Computer controlled separately excited dc motor experimental station for performing load test / Muhammad Russedy Awang - Awang, Muhammad Russedy (1995)
This project is regarding the development of computer controlled separately excited dc motor experimental station capable of performing load test. A variable speed drive is provided by the single-phase full wave thyristor controlled rectifier supplying the required variable voltage to the armature of the test machine. All experimental data measured by the transducers are acquired automatically and transmitted into the computer sequence by the latching circuit through serial interfacing unit. The operation of the station is controlled by software program written in Quick-Basic language.